Phenotypic Discovery of SB1501, an Anti‐obesity Agent, through Modulating Mitochondrial Activity. (10th March 2021) - Jo, Ala; Kim, Mingi; Kim, Jong In; Ha, Jaeyoung; Hwang, Yoon Soo; Nam, Hyunsung; Hwang, Injae; Kim, Jae Bum; Park, Seung Bum
Abstract: Obesity has become a pandemic that threatens the quality of life and discovering novel therapeutic agents that can reverse obesity and obesity‐related metabolic disorders are necessary. Here, we aimed to identify new anti‐obesity agents using a phenotype‐based approach. We performed image‐based high‐content screening with a fluorogenic bioprobe (SF44), which visualizes cellular lipid droplets (LDs), to identify initial hit compounds. A structure‐activity relationship study led us to yield a bioactive compound SB1501, which reduces cellular LDs in 3T3‐L1 adipocytes without cytotoxicity. SB1501 induced the expression of gene products that regulate mitochondrial biogenesis and fatty acid oxidation in 3T3‐L1 adipocytes. Daily treatment with SB1501 improved the metabolic states of db/db mice by reducing body fat mass, adipose tissue mass, food intake, and increasing glucose tolerance. The anti‐obesity effect of SB1501 may result from perturbation of the PGC‐1α–UCP1 regulatory axis in inguinal white adipose tissue and brown adipose tissue. These data suggest the therapeutic potential of SB1501 as an anti‐obesity agent via modulating mitochondrial activities. Abstract : Enhancing energy expenditure : By monitoring cellular lipid droplets with a fluorogenic bioprobe against a small‐molecule library, we discovered a bioactive compound, SB1501, that reduced fat accumulation by elevating mitochondrial biogenesis and fatty acid oxidation via the PGC‐1α–UCP1 pathway. SB1501 also showed anti‐obesity effects in vivo, resulting in reduced fat accumulation of IWAT/BAT, decreased body weight, and lower insulin resistance.